Strong convergence theorems for solving pseudo-monotone variational inequality problems and applications. (2nd December 2022) - Liu, Liya; Qin, Xiaolong
Abstract : In this paper, we introduce two different kinds of iterative algorithms, which are based on the inertial Tseng's method and the viscosity method. They are intended to solve the variational inequality problems governed by the mappings of pseudo-monotone type. Strong convergence theorems are established in Hilbert spaces. Practical examples in fuzzy environment are given to show the applicability and effectiveness of the proposed algorithms.